186 Effects of a Phytogenic Feed Additive (Aromex® Pro) and Narasin (Skycis®) on Finishing Pig Growth Performance and Carcass Characteristics - Ewing, Kristen M (J Anim Sci, 2021)
Feed additives are commonly used in finishing pig diets to improve growth performance and carcass characteristics; however, data is limited on the interaction of various feed additives. The objective of this study was to determine the individual and combined effects of a phytogenic feed additive (Aromex(®) Pro) and narasin (Skycis(®)) on finishing pig growth performance and carcass characteristics. The study was conducted at a commercial research facility using a RCBD with 4 dietary treatments: Control (no Aromex(®) Pro or Skycis(®)); Aromex (as Control with 90.7 g/ton Aromex(®) Pro); Skycis (as Control with 13.6 g/ton Skycis(®)); Aromex + Skycis (as Control with 90.7 g/ton Aromex(®) Pro and 13.6 g/ton Skycis(®)). Diets were based on corn, soybean meal, and corn germ meal and were fed using a 3-phase program. Diets were formulated to the same nutrient levels across treatments that met or exceeded nutrient recommendations (NRC, 2012), with the feed additive added at the expense of corn. Pigs were placed on test at 40.6 ± 4.7 kg and harvested in 2 equal groups at 122.4 ± 2.2 kg. Thirteen blocks were used with pens of 34 pigs for 1,768 total pigs. Data were analyzed using PROC MIXED of SAS with pen as the experimental unit, fixed effect of treatment, and random effect of block. There was no effect (P > 0.05) of treatment on start or end weights, overall ADG (live or carcass weight), overall ADFI, or any carcass characteristics. Overall G:F (live and carcass weight) for Aromex and Skycis was similar (P > 0.05) to each other and greater (P < 0.05) than Control. Aromex + Skycis had G:F (live and carcass weight) similar to Control and Aromex, but less than Skycis. In conclusion, including Aromex(®) Pro and Skycis(®) in finishing diets improved feed efficiency, but those effects were not additive. [Image: see text]